2019
DOI: 10.1371/journal.pone.0210273
|View full text |Cite
|
Sign up to set email alerts
|

Identification of whole blood mRNA and microRNA biomarkers of tissue damage and immune function resulting from amphetamine exposure or heat stroke in adult male rats

Abstract: This work extends the understanding of how toxic exposures to amphetamine (AMPH) adversely affect the immune system and lead to tissue damage. Importantly, it determines which effects of AMPH are and are not due to pronounced hyperthermia. Whole blood messenger RNA (mRNA) and whole blood and serum microRNA (miRNA) transcripts were identified in adult male Sprague-Dawley rats after exposure to toxic AMPH under normothermic conditions, AMPH when it produces pronounced hyperthermia, or environmentally-induced hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
(90 reference statements)
3
5
0
Order By: Relevance
“…According to our results, miR-122 expression showed large increases in the liver tissue and very low increases in the plasma in LDLT patients, which agrees with a previous study in adult male rats [9]. Particularly hepatic miR-122 was detected in the native liver following LDLT.…”
Section: Discussionsupporting
confidence: 92%
“…According to our results, miR-122 expression showed large increases in the liver tissue and very low increases in the plasma in LDLT patients, which agrees with a previous study in adult male rats [9]. Particularly hepatic miR-122 was detected in the native liver following LDLT.…”
Section: Discussionsupporting
confidence: 92%
“…Gene expression profiles in the lung tissue of an HS rat model showed that the miRNAs associated with inflammatory/immune responses, including leukocyte migration, lipopolysaccharide response, NIK/NF-kappaB signaling, and response to reactive oxygen species, were upregulated, which is in agreement with our findings (18). Whole blood mRNA and microRNA have been identified as biomarkers of tissue damage and immune function resulting from HS (19).…”
Section: Discussionsupporting
confidence: 91%
“…The gene expression pro les in lung of a HS rat model reveals that the miRNAs related to in ammatory/immune responses, including leukocyte migration, response to lipopolysaccharide, NIK/NF-kappaB signaling, and response to reactive oxygen species, are up-regulated, which is consistent with our results [11]. Whole blood mRNA and microRNA was identi ed as biomarkers of tissue damage and immune function resulting from heat stroke exposure [12].…”
Section: Discussionsupporting
confidence: 88%